Modeling, analysis and testing of autonomous operation of an inverter-based microgrid - Pogaku,N; Prodanovic,M; Green,TC (IEEE Transactions on Power Electronics, 2007)
The analysis of the small-signal stability of conventionalpower systems is well established, but for inverter basedmicrogrids there is a need to establish how circuit and controlfeatures give rise to particular oscillatory modes and which ofthese have poor damping. This paper develops the modeling andanalysis of autonomous operation of inverter-based microgrids.Each sub-module is modeled in state-space form and all arecombined together on a common reference frame. The modelcaptures the detail of the control loops of the inverter but not theswitching action. Some inverter modes are found at relatively highfrequency and so a full dynamic model of the network (ratherthan an algebraic impedance model) is used. The complete modelis linearized around an operating point and the resulting systemmatrix is used to derive the eigenvalues. The eigenvalues (termed“modes”) indicate the frequency and damping of oscillatorycomponents in the transient response. A sensitivity analysis is alsopresented which helps identifying the origin of each of the modesand identify possible feedback signals for design of controllersto improve the system stability. With experience it is possible tosimplify the model (reduce the order) if particular modes arenot of interest as is the case with synchronous machine models.Experimental results from a microgrid of three 10-kW invertersare used to verify the results obtained from the model.